Growth of Stone pine (Pinus pinea L.) European provenances in central Chile - Loewe Muñoz, Verónica (2016)
Pinus pinea is characterized by phenotypic plasticity, tolerance to harsh soils and climates, but low differentiation in growth parameters and low genetic variability. Growth and cone production of six European stone pine provenances (two from Italy, three from Spain and one from Slovenia) were analyzed in a field trial experiment established in central Chile. The study evaluated height, diameter at breast height (DBH) and crown diameter growth of 147 nineteen-year-old trees per provenance, as well as fruiting variables (i.e., number of cones per tree and cone weight). Survival over the first 7 years was also evaluated. Provenances significantly differed in cone number per tree, cone weight, height and DBH growth, and crown diameter growth. Provenances were grouped according to growth and production variables: one group included the Italian and Slovenian provenances, the second group Andalucía and Sierra Morena (Spain), and the third included Meseta Castellana (Spain). Individual cone production was positively correlated with cone weight and other growth variables. Meseta Castellana provenance showed the highest growth and productivity. Our results provide useful information for the selection of P. pinea provenances to be used in new plantations in central Chile.